Willingness and attitudes of the general public towards the involvement of medical students in their healthcare - Abu Jubain, Mariam; Alobaidi, Hajar; Bholah, Sanah; Kanani, Farah; Koghar, Raveen; Sitch, Alice; Shereef, Hannah (Canadian Medical Education Journal, 2012)
Objectives: To determine if patients allow medical students to perform less invasive procedures compared to more invasive procedures, and how this is related to patient demographics and previous experience with medical students. Methods: A cross-sectional survey was conducted in six areas of Birmingham, UK. All members of the general public over the age of 18 were eligible, excluding non-English speaking people and those with cognitive impairments. Respondents were asked to rank their willingness for medical students to perform history taking/examinations and clinical procedures of varying degrees of invasiveness. Results: We received a total of 293 responses. For both history taking/examinations and clinical procedures, people were more willing to allow medical students to perform less invasive procedures rather than more invasive procedures. White and older people were more willing to allow all history taking/examinations procedures; additionally, women were more willing to allow history taking. White, female, and older participants were more willing to allow blood pressure measurement; whilst older people and those with previous experience were more willing to allow venepuncture. No significant associations were found for intubation. Conclusions: The public is less willing for medical students to perform more invasive procedures. This may severely limit opportunities to attain clinical competencies.